Fine‐Tuning the 3D Structure of Nonfullerene Electron Acceptors Toward High‐Performance Polymer Solar Cells. (20th April 2015) - Li, Haiyan; Hwang, Ye‐Jin; Courtright, Brett A. E.; Eberle, Frank N.; Subramaniyan, Selvam; Jenekhe, Samson A.
<x xml:space="preserve">Abstract</x> Arylene linkers in a series of new tetraazabenzodifluoranthene diimide dimers enable tuning of the 3D molecular structure of nonfullerene electron acceptors, facilitating observation of dramatic variation of the power conversion efficiency from 2.6% to 6.4% as the twist angle between the monomeric building blocks in the dimer is varied.